Acute Calcific Tendinitis of the Index Finger in a Child. (September 2017) - Walocko, Frances M.; Sando, Ian C.; Haase, Steven C.; Kozlow, Jeffrey H.
Background: Calcific tendinitis is characterized by calcium hydroxyapatite crystal deposition within tendons and is a common cause of musculoskeletal pain in adults. Its clinical manifestations may be acute, chronic, or asymptomatic. Acute calcific tendinitis is self-resolving condition that is rarely reported in the pediatric population and may be overlooked for more common processes, leading to unnecessary treatment.Methods: A chart reivew was performed of a single case of acute calcific tendonitis of the index finger in a child.Results: We describe a case of calcific tendinitis of the index finger in a 9-year-old boy who was referred to us for a second opinion after surgical exploration of an acutely inflamed digit was recommended based on his initial presentation. The calcifications and symptoms resolved over time without operative management.Conclusions: Although rare in children, acute calcific tendinitis can present similar to an infection. However, appropriate managment is non-operative as the symptoms and radiographic findings resolve over time.